Penggunaan E-Modul untuk Meningkatkan Hasil Belajar Pendidikan Pancasila Siswa Sekolah Dasar: Sebuah Tinjauan Sistematis: The Use of E-Modules to Improve Elementary School Students' Pancasila Education Learning Outcomes: A Systematic Review - Asthadi Mahendra Bhandesa; Ngurah Pujawan; I Wayan Widiana; Surya Mahayanti; I Made Sudarsana (ITScience (Information Technology and Science), 2025)
E-Modules are systematically structured electronic teaching materials that incorporate multimedia elements, such as video, images, and audio, to enhance student learning experiences. The purpose of this study is to conduct a systematic review of the use of E-Modules to improve elementary school students' Pancasila Education learning outcomes. The research method employed a review of five databases and a systematic search. Following the PRISMA guidelines, the included studies evaluated elementary school students' Pancasila Education learning outcomes and described the use of E-Modules. The results demonstrate the effectiveness of E-Modules in improving elementary school students' Pancasila Education learning outcomes. The use of E-Modules has consistently improved learning quality. The integration of innovative approaches and local wisdom content in e-modules has been empirically proven to achieve a very high level of expert validity and has received positive practical responses from both educators and students. The use of this instrument is not only effective in optimising cognitive learning outcomes and material mastery, but also has a strategic impact on strengthening the dimensions of the Pancasila Student Profile and students' critical thinking skills. This study also found the importance of using E-Modules to transform conventional teaching materials into a more interactive format and to support the development of 21st-century Education, making it easier for educators and more effective at improving the experience and learning outcomes of elementary school students.